2001
DOI: 10.1046/j.1461-9563.2001.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Population abundance and movement of Frankliniella species and Orius insidiosus in field pepper

Abstract: Summary1 A recent study revealed the capacity of the Orius insidiosus to suppress populations of Frankliniella spp. in field pepper during the spring when thrips are rapidly colonizing and reproducing. In this study, population abundance in pepper during spring, summer, and autumn was determined to understand better predator/prey dynamics under local conditions. Local movement between pepper flowers also was quantified to examine how population attributes of the predator allow suppression of rapidly moving pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 14 publications
3
65
0
1
Order By: Relevance
“…Pepper is a suitable reproductive host for Frankliniella species, thus making primary and secondary disease cycles of thrips-vectored pathogens possible (see Puche et al 1995). Conversely, pepper also is a suitable host for many important natural enemies, such as Orius insidiosus (Say) (Heteroptera: Anthocoridae) and Geocoris punctipes (Say) (Heteroptera: Lygaeidae), that are capable of suppressing thrips populations (Schoenig and Wilson 1992, Funderburk et al 2000, Ramachandran et al 2001. However, if UV reßective mulch interferes with the ability of natural enemies to locate prey, its use could disrupt these valuable natural control mechanisms (see Parker 1969, Freund andOlmstead 2000, for role of vision in predatory Heteroptera).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Pepper is a suitable reproductive host for Frankliniella species, thus making primary and secondary disease cycles of thrips-vectored pathogens possible (see Puche et al 1995). Conversely, pepper also is a suitable host for many important natural enemies, such as Orius insidiosus (Say) (Heteroptera: Anthocoridae) and Geocoris punctipes (Say) (Heteroptera: Lygaeidae), that are capable of suppressing thrips populations (Schoenig and Wilson 1992, Funderburk et al 2000, Ramachandran et al 2001. However, if UV reßective mulch interferes with the ability of natural enemies to locate prey, its use could disrupt these valuable natural control mechanisms (see Parker 1969, Freund andOlmstead 2000, for role of vision in predatory Heteroptera).…”
mentioning
confidence: 99%
“…Other Þeld studies have shown that O. insidiosus is capable of rapidly colonizing plants and suppressing Frankliniella spp. (Funderburk et al 2000, Ramachandran et al 2001). However, this valuable naturally occurring control may be disrupted if UV-reßective mulches retard colonization by natural enemies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ecologically, western flower thrips is highly polyphagous and capable of reproducing on numerous host plants (Northfield et al, 2008;Paini et al, 2007). As large populations can develop on non-crop hosts, mass dispersal into crops occurs, whether open field crops (Pearsall & Myers, 2001;Puche et al, 1995;Ramachandran et al, 2001) or crops in protected environments (Antignus et al, 1996). The potential for continual recolonization of crops limits the observed field efficacy of insecticides (Eger et al, 1998;Reitz et al, 2003).…”
Section: Western Flower Thrips As An Invasive Speciesmentioning
confidence: 99%
“…Consequently, there is the potential for secondary virus spread from within the crop (Gitaitis et al, 1998). However, Funderburk et al (2000) demonstrated that the predator Orius insidiosus (Say) colonizes peppers and can effectively suppress thrips populations in the crop (Funderburk et al, 2000;Ramachandran et al, 2001). In particular, O. insidiosus preferentially preys on western flower thrips over the native species F. tritici and F. bispinosa (Baez et al, 2004;Reitz et al, 2006).…”
Section: Biological Controlmentioning
confidence: 99%